PEMBELAJARAN KOOPERATIF DENGAN PENDEKATAN EXPERIENTAL LEARNING UNTUK MENINGKATKAN KETERAMPILAN SOSIAL - Indrastoeti, Jenny; Mahfud, Hasan (Universitas Pendidikan Indonesia, 2015)
The purpose of this research is (1) to improve the social skill of elementary school students, (2) finding adequate instructional design model to improve students’ social skill. The research is conducted at the classroom action research consists of two cycles, every cycle consists of planning, action, observation, and reflection. The average value of Social Skills students in a cycle one is 62.01 and 72.52 in the two cycles. The percentage asset value in the classical mastery of social skills is 40% in cycle 1 and 85.85% in cycle 2. Based on the result, the conclusions are: 1) Model cooperative learning with experiential learning approach, can improve students' social skills. (2) Instructional design to improve the social skills of students in learning social study is a model of cooperative learning with experiential learning approach.Keywords: cooperative model, experiental learning, social skill.